Information and Communication Technology (ICT) for Agricultural Development: Factors Associated With Computer Utilization at Area Farmers Organizations in Peninsular Malaysia - Omar, Bahiyah (2003)
The utilization of Information and Communication Technology [ICT] is believed to bring positive impact on productivity and competitiveness in all sectors including the agricultural sector. This is because ICT promotes efficiency through cost and time saving and enhances information synergies through sharing of information and pooling of resources. However, Malaysian agricultural sector is still lagging behind in ICT development as compared to the manufacturing and banking sectors. Since ICT has always been associated with computer technology, this study was carried out to determine factors associated with computer utilization in one of the important organizations in Malaysian agricultural sector that is the farmers' organization. The factors examined in this study include individual, organizational and technological factors. The selection of the independent variables was based on Rogers' model of diffusion of innovation. Meanwhile, computer utilization was measured in terms of intensity, frequency and diversity of use. The relationships between independent variables and computer utilization were also sought in determining factors that influence computer utilization at farmers' organizations. Data collection was carried out via mail by using self-administered questionnaires. A total of 209 respondents from 23 area farmers organizations [PPKs] were involved in this study. The data were analyzed using Statistical Package for Social Sciences [SPSS] version 10.1 and the findings were presented using descriptive statistics and Spearman Rho correlation. The findings of this study revealed that the levels of respondents' attitude towards computer and their perception on technological factors were high. The levels of computer literacy and facilitating conditions were moderate. Meanwhile, the level of communication channels use was low. The findings also showed that respondents with better education, more positive cognitive attitude, higher computer literacy [i.e: computer knowledge and skills], more usage of communication channels [i.e: interpersonal and mass media], better perception on relative advantages of computer and lower perception of computer complexity, utilize computer more in the organization. In conclusion, computer utilization could be improved by encouraging participations in ICT programs, providing sufficient and up-to-date computer trainings to all individuals, acculturating ICT related-activities in the organization and forming IT unit or employing dedicated person(s) to provide internal supervision on computer use and to deal with hardware or software difficulties.